The Exploitation of Wetland Ecosystems by Herbivores on Bylot Island - Gauthier, Gilles; Rochefort, Line; Reed, Austin (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary We examine the interactions between herbivores, plants and climatic factors inarctic wetlands using, as a case study, results of our research on grazing by snow geese on Bylot Island. During the summer, geese are the most important herbivore on the island and consume a high proportion of the annual graminoid production (grasses and sedges). Herbivores can sometimes enhance plant production by increasing the turnover rate of nitrogen, a nutrient which commonly limits growth of arctic plants. However, we found no evidence of positive feedback of grazing on plant growth and, on the contrary, chronic goose grazing tended to decrease production of these ecosystems in the long term. Geese need large quantities of high-quality plants to breed successfully, and negative effects on goose reproduction as a result of lack of food were detected. Herbivore populations are also influenced by climatic factors, either directly or indirectly through effects on plant growth. It is likely that tundra plant-herbivore systems will be strongly affected by future climatic changes.